Baboon Fibrinogen Adsorption and Platelet Adhesion to Polymeric Materials - Chinn, Joseph A; Horbett, Thomas A; Ratner, Buddy D (Thrombosis and Haemostasis, 1991)
The role of fibrinogen in mediating platelet adhesion to polymers exposed to blood plasma was studied by comparison of the effect of plasma dilution on fibrinogen adsorption and platelet adhesion, and by the use of coagulation factor deficient plasmas. Polyetherurethane substrates were first preadsorbed with dilute plasma, then contacted with washed platelets suspended in a modified, apyrase containing Tyrode’s buffer. Platelet adhesion was studied under static conditions in Multiwell dishes, and also under shearing conditions using a parallel plate perfusion chamber. Fibrinogen adsorption and platelet adhesion were measured using 125I radiolabeled baboon fibrinogen and min radiolabeled baboon platelets, respectively. Surfaces were characterized by electron spectroscopy for chemical analysis (ESCA).When fibrinogen adsorption to Biomer was measured after 2 h contact with a series of dilute plasma solutions under static conditions, a peak in adsorption was observed from 0.26% plasma, i.e., adsorption was greater from 0.26% plasma than from either more or less dilute plasma. A peak in subsequent platelet adhesion to the plasma preadsorbed surfaces, measured after 2 h static incubation with washed platelets, was also observed but occurred on Biomer preadsorbed with 1.0% plasma.When fibrinogen adsorption was measured after 5 min contact under shearing conditions, the fibrinogen adsorption peak occurred on surfaces that had been exposed to 1.0% plasma. A peak in platelet adhesion to these preadsorbed surfaces, measured after 5 min contact with the platelet suspensions under shearing conditions, was observed on Biomer preadsorbed with 0.1% plasma. Shifts between the positions of the peaks in protein adsorption and platelet adhesion occurred on other polymers tested as well.Platelet adhesion was almost completely inhibited when baboon and human plasmas lacking fibrinogen (i. e., serum, heat defibrinogenated plasma, and congenitally afibrinogénémie plasma) were used. Platelet adhesion was restored to near normal when exogenous fibrinogen was added to fibrinogen deficient plasmas. Adhesion was also inhibited completely when a monoclonal antibody directed against the glycoprotein IIb/IIIa complex was added to the platelet suspension. Platelet adhesion to surfaces preadsorbed to von Willebrand factor deficient plasma was the same as to surfaces preadsorbed with normal plasma.While it appears that surface bound fibrinogen does mediate the initial attachment of platelets to Biomer, the observation that the fibrinogen adsorption and platelet adhesion maxima do not coincide exactly also suggests that the degree of subsequent platelet adhesion is dictated not only by the amount of surface bound fibrinogen but also by its conformation.